Hubungan Antara Paritas Ibu Dengan Pelaksanaan Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4K) - mardliyana, nova elok (Universitas Muhammadiyah Surabaya, 2022)
Program Planning of Birth and Prevention of Komplikasi (P4K) represent a program with aim to increase knowledge, attitude, behavioral of pregnant mother, family and husband about the importance of planning of copy. Parity represent result of reproduction from a woman which is being by to the number of borne by child is life during a period of/to reproduction. Ms. with high parity more owning experience of dalan face copy. And efficacy or do not from the experience will influence storey;level compliance of them to health workers.Objective : to find out the relationship between maternal parity and the implementation of the planning and prevention program for complicationsMethods: This research of analytic method use with approach of sectional cross, election of sampel with type sampling probability of simple sampling random with amount 46 responden. obtained data use last questioner later, then with test of statistic SPSS square chi.Results: Test of statistic SPSS square chi got by result of p = 0,001 smaller than = 0,05. Hence decided by Ho refused and H1 accepted by hence its meaning there is relation between mother parity with execution of P4K in work region Puskesmas Sawahan.Conclusion: At this research is obtained by conclusion that mother parity excecution progressively lower behavior of health of mother. And for expected to next researcher to conduct furthermore research about execution of P4K with more complex factor.